2018
DOI: 10.1002/andp.201700427
|View full text |Cite
|
Sign up to set email alerts
|

Optical Switch Based on Dressed Intracavity Dark States

Abstract: We present a scheme to realize two-direction optical switch by a single-mode optical cavity containing some four-level atoms. The high switching efficiency can be obtained through low photon loss and large third-order nonlinear susceptibility of this N-type atomic system in cavity. Without the microwave source, it can be reduced to a -type atomic system where a coupling laser is used to realize single intracavity electromagnetically induced transparency (EIT). Namely, the probe field can be transmitted almost … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Referring to the results in Ref. [43], we have already given a general explanation of VF-EIT by adding an extra field so as to enrich the coupling process. This system of Guo et al studied an N-type fourlevel QE and discussed the contribution of a microwave field added to couple the two ground states.…”
Section: Characteristic Output Propertiesmentioning
confidence: 91%
See 2 more Smart Citations
“…Referring to the results in Ref. [43], we have already given a general explanation of VF-EIT by adding an extra field so as to enrich the coupling process. This system of Guo et al studied an N-type fourlevel QE and discussed the contribution of a microwave field added to couple the two ground states.…”
Section: Characteristic Output Propertiesmentioning
confidence: 91%
“…In previous theoretical research on cavity QED systems, the ideal switching contrasts have been achieved in more complex systems such as a coupled-resonator array (the number is 7) [13] and three empty cavities [12] as the cavity, or a multiple-level quantum emitter (energy level> 3). [43] Wang et al demonstrated that only at a certain probe light-QE detuning and coupling strength, the resonant photons are completely reflected and the cavity QED system could be regarded as a…”
Section: Switching Contrastmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, it is becoming more and more important to realize and modify intracavity EIT [10][11][12][13][14][15][16][17] in cavity quantum electrodynamics (cavity-QED) systems [18,19]. Comparing with intracavity EIT itself, the modified intracavity EIT has more advantages on light controlling light system, such as low light intensity of switching field and high switching efficiency [12,13,20,21].…”
Section: Introductionmentioning
confidence: 99%